Housing characteristics of households with wheeled mobility device users from the American Housing Survey: do people live in homes that facilitate community participation?. Issue 1 (1st January 2016) - Greiman, Lillie; Ravesloot, Craig
Abstract: For people with mobility impairments, having an accessible and usable home environment is a critical factor in their ability to live independently and participate in their communities. However, the status of home accessibility in the American housing stock is largely unknown. The purpose of this study was to examine accessibility of the American housing stock using the American Housing Survey. We analyzed data from the 2011 American Housing Survey to examine the accessibility of housing units across six groups defined by home ownership and impairment status. High levels of home inaccessibility across all groups and all variables were evident. Developing accessible housing stock is critical to community development in that it can support opportunities for increased participation and employment for people with disabilities. This study provides a basis for more specific studies regarding housing access and the potential impact of housing policy changes that could increase community access for people with mobility impairments.